STRATEGIES USED FOR EMPHASIS IN KIMUTHAMBI - Ireri, Humphrey Kirimi (Advances in Social Sciences Research Journal, 2016)
Emphasis is inherent in everyday communication and is very important in relationships, leadership, peace building and success in virtually every area of livelihood. This study’s main goal is to provide an analysis of emphasis in Kimuthambi. The objective of the study is to identify and discuss strategies used for emphasis in Kimuthambi. The study is guided by the relevance theory by Sperber and Wilson. It utilizes both qualitative and quantitative research designs and is carried out in Muthambi Division, Tharaka Nithi County, Kenya. The population includes all the Kimuthambi communicative events. The researcher purposively sampled ten real life communicative events conducted in Kimuthambi which involved forteen speakers. Data was collected using a digital audio recorder and an observation schedule. The recorder captured conversations in Kimuthambi in the selected communicative events and the observation schedule was used to record the contextual information. The researcher transcribed utterances from the data collected that utilizes stragetegies used for emphasis. The transcribed utterances are one hundred and thirty six. Then guided by the communicative principle of relevance, the researcher identifies and discusses fifty two utterances used for emphasis in Kimuthambi. The study establishes that emphasis in Kimuthambi is mainly through the use of intensifiers and repetition. This study enhances the analysis of Kimuthambi as a language variety and adds to the existing knowledge on strategies of emphasis in various languages of the world.